Synthesis and characterization of the new thiazole Schiff base 2-(2-hydroxy) naphthylideneaminobenzothiazole and its complexes with Co(II), Cu(II), and Ni(II) ions - Saydam, S (Marcel Dekker Inc, 2002)
The new ligand 2-(2-hydroxy)naphthylideneamitiobenzothiazole has been synthesised from 2-aminobenzothiazole and 2-hydroxynaphthylaldehyde by condensation in ethanol. Metal complexes of the ligand were prepared with chloride salts of Co(II), Cu(II), and Ni(II) in ethanol. The ligand and its complexes have been characterised by microanalyses, magnetic susceptibility, thermogravimetric analysis, FT-IR, C-13, H-1 NMR, and UV-Visible spectroscopy. From these findings, it is suggested that two ligands coordinate to each metal atom by hydroxyl and the imino nitrogen to form high-spin tetrahedral complexes with Co(II) and Ni(II) while forming diamagnetic binuclear complex with Cu(II).
Keywords: Transition-Metal Complexes; Thiosemicarbazones